APPLICATIONOF INVENTORY GOODS IN "PT.DUTABENHIL "USINGMICROSOFT ACCESS 2003 - Eric Harvian (Jurnal Manajemen Informatika, 2010)
Scientific writing contains a simple program on the computerized inventory, using the inputpurchasing goods through the transaction, which will then automatically stored in a database andwill exit the display output to be received by the customer or purchaser as the invoice or receipt andviewing reports required by the company. Scientific Writing is supported by Microsoft Access 2003Programming Language through the process of inputting and sales of computerized this makes dataprocessing more efficient and accurate and can provide information on existing inventory.